Differential responses to nanoparticles induced by nanocarbon application in pigmented rice seedlings - S. Samart; S. Chutipaijit (My University, 2020)
To investigate the effects of nanocarbon on physiological responses of plant growth, contents of photosynthetic pigments, and the activities of antioxidant enzymes in the seedlings of pigmented rice cv. Hom-nin that were cultured on either untreated-nanocarbon (control) or treated-nanocarbon (soil:nanocarbon, 8:1, 6:1, 2:1 w/w) were studied. The results showed that growth performances, photosynthetic pigment contents and antioxidant enzyme activities in seedlings 7–28 days after the treated-nanocarbon were significantly differenced when compared to the control treatment. Growth performances, photosynthetic pigment contents and antioxidant enzyme activities in pigmented rice seedlings were significantly enhanced by the low and moderate concentrations of nanocarbon treatments (soil:nanocarbon, 8:1, 6:1 w/w) for all sampling dates (7, 14, 21 and 28 days after the nanocarbon treatments). While at the high concentration of nanocarbon (soil:nanocarbon, 2:1 w/w) treatment, growth performances, photosynthetic pigment contents and antioxidant enzyme activities in pigmented rice seedlings were significantly decreased when compared to the other treatments. The results suggested that the inducible physiological responses in pigmented rice seedlings to nanocarbon depend on both the concentrations and the exposure duration. The appropriate ratio of 8:1 and 6:1 w/w of soil:nanocarbon seemed to induce the physiological performances in the seedlings, more than those at the high concentration and untreated of nanocarbon.
Keywords: Nanoparticles: synthesis and applications